Profitability of green hydrogen production and feasibility of waste heat integration to DHS in the Ísafjörður’s energy system: A techno-economic analysis - Víðisdóttir, Elena Dís (UiT The Arctic University of Norway, 2022)
Hydrogen production by electrolysis using renewable energy sources is essential for hydrogen to be able to contribute to the green energy transition. Producing the hydrogen on the site of use minimizes the transportation costs and footprint, and utilization of all by-products increases the electric efficiency of hydrogen production. During hydrogen production by electrolysis the chief part of energy losses are in the form of thermal energy or heat. This thesis evaluates the profitability of a small-scale electrolytic hydrogen production in northwest Iceland and the feasibility of waste heat integration to the local district heating system. Here we show that the hydrogen production is profitable for a broad range of operation scenarios, hydrogen selling prices and electricity prices and that the integration of waste heat is feasible to the low temperature district heating plant in Ísafjörður. A sensitivity study is conducted for the calculations, for a optimistic, realistic and pessimistic scenario. The heat integration saves 13, 7 and 2% of the annual power consumption for the district heating plant for each scenario respectively. The waste heat integration affects the efficiency of the electrolyser, increasing it by 3.7% for the optimistic scenario. The economic effects of waste heat integration were found to be small. The heat integration was found to save a maximum of 5% of the DHS annual power costs. The waste heat sale revenue of the hydrogen production was found to be maximum 1.7% of net sales, which are hydrogen and heat sales in this thesis. The financial analysis of the hydrogen production conducted as a sensitivity study of an optimistic, realistic, and pessimistic scenario show that the hydrogen prices required for the project to reach profitability are 1.5 €, 3 € and 6 € per kg hydrogen when electricity prices are up to 24 €/MWh. This thesis is anticipated to spur for further research on the feasibility of hydrogen production with waste heat utilization in cold areas in Iceland, where no geothermal ...